2018
DOI: 10.1002/hbm.23906
|View full text |Cite
|
Sign up to set email alerts
|

Four‐way multimodal fusion of 7 T imaging data using an mCCA+jICA model in first‐episode schizophrenia

Abstract: Acquisition of multimodal brain imaging data for the same subject has become more common leading to a growing interest in determining the intermodal relationships between imaging modalities to further elucidate the pathophysiology of schizophrenia. Multimodal data have previously been individually analyzed and subsequently integrated; however, these analysis techniques lack the ability to examine true modality inter-relationships. The utilization of a multiset canonical correlation and joint independent compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 87 publications
(124 reference statements)
2
15
0
Order By: Relevance
“…GMV reduction in these regions, which are involved in important sensorimotor and cognitive functions, is consistent with previous MRI studies on SSD patients (Iwashiro et al, 2012;Kikinis et al, 2010;Koo et al, 2008;Shimizu et al, 2007;Tang et al, 2012;Torii et al, 2012;Zhou et al, 2005). Furthermore, the present study is in line with the recent mCCA + jICA study by Lottman and colleagues (Lottman et al, 2018), once again highlighting the relationship between GMV alterations and aberrant INA in SSD.…”
Section: Group Differencessupporting
confidence: 93%
See 2 more Smart Citations
“…GMV reduction in these regions, which are involved in important sensorimotor and cognitive functions, is consistent with previous MRI studies on SSD patients (Iwashiro et al, 2012;Kikinis et al, 2010;Koo et al, 2008;Shimizu et al, 2007;Tang et al, 2012;Torii et al, 2012;Zhou et al, 2005). Furthermore, the present study is in line with the recent mCCA + jICA study by Lottman and colleagues (Lottman et al, 2018), once again highlighting the relationship between GMV alterations and aberrant INA in SSD.…”
Section: Group Differencessupporting
confidence: 93%
“…The procedure was similar to that described by and Lottman et al (2018). In a first step, two-tailed for multiple comparisons using the false discovery rate (FDR) method (Benjamini & Hochberg, 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other word, the spatial maps of different modalities in one IC are correlated between modalities, while spatial maps of different ICs are independent with each other. A previous study conducted multimodal fusion analysis using mCCA-jICA and found results supporting and extending previous findings derived from single modality analyses, and also provided a more comprehensive understanding of the underlying relationship between functional and structural abnormalities in schizophrenia ( Lottman et al, 2018 ). Furthermore, these selected group-discriminating components might be useful for diagnosing schizophrenia ( Sui et al, 2013a , Yang et al, 2010 ).…”
Section: Introductionsupporting
confidence: 77%
“…One popular approach for combining multimodal biomarkers of disease states is joint ICA (jICA), which concatenates two or more modalities into a single data stream (Sui et al, 2011). Lottman et al (2018), for instance, combined measures of gray matter, white matter, cerebrospinal fluid, and the amplitude of low-frequency fluctuations into a single jICA model, toward successful differentiation of first-episode schizophrenia patients and controls (Lottman et al, 2018). Similarly, Ouyang et al (2015) combined both gray matter volume and white matter functional anisotropy profiles into a single jICA model, toward the identification of multimodal features that distinguished Alzheimer's patients from controls.…”
Section: Multivariate Approachesmentioning
confidence: 99%